Pengaruh Metode Qira`ati Terhadap Kemampuan Membaca Al-Qur’an - Eva Shofiyatun Nisa; Dewi Maharani (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
This research was motivated by the lack of teacher creativity in conveying the material, some students were less careful in paying attention to makharijul letters and the rules of tajwid, and the lack of awareness of parents in motivating students, causing students' ability to read the Qur'an to be hampered and less than optimal. This study aims to determine the extent of the influence of the Qira'ati method on the ability to read the Qur'an. This type of research is quantitative research with a descriptive approach. The location understudy is MIN 1, South Tangerang City. The sample in this study was all students finishing class totaling 32 people. While the sampling technique is using the sampling population. It is kind of a technique that takes from the whole population number. The data collection is done by using the questionnaire method. The analysis technique used is a sample linear regression analysis, from hypothesis testing in research using the t-test. The results of research conducted by researchers managed to obtain data on the effect of the Qira’ati Method on the Ability to Read the Qur'an of 5.357 ≥ 2.042. It is proven that ≥ 5% significance level with db of 2.042, then H0 is rejected and Ha is accepted. It means that there is a significant influence between the Qira'ati method on the ability to read the Qur'an.